Embankment overtopping protection by riprap considering interstitial flow - Wahl, Tony L., author; Colorado State University. Department of Engineering, publisher (Colorado State University. Libraries, 2016)
Riprap is commonly provided to protect embankment slopes from localized erosion caused by surface runoff during rainfall events, but it can also provide erosion protection during small overtopping events. When flow rates are small, most water may flow interstitially through the riprap layer, then gradually above the riprap layer as flow rates increase. On relatively steep slopes, interstitial flow may still be a significant proportion of the total flow—even 100% of the flow—when the failure discharge is reached. In the late 1990s the Bureau of Reclamation sponsored tests on 2H:1V (50%) embankment slopes to determine allowable rates of overtopping flow for large riprap with median stone sizes up to 26-inch diameter. These tests included measurements of interstitial flow, and Mishra (1998) and Frizell et al. (1998) used the collected data to develop a design procedure for riprap on steep slopes accounting for interstitial flow. Unlike other riprap design equations that relate allowable discharge or stone size to independent variables through simple closed-form equations, the method incorporates interstitial flow in a mechanistic way through iterative calculations that add complexity to the solution process. This paper illustrates the Mishra/Frizell design method through example calculations and highlights key aspects of the solution process. Important conclusions are drawn related to the use of riprap for overtopping flow protection on typical embankment dam slopes.
Presented at the Protections 2016: 2nd international seminar on dam protection against overtopping: concrete dams, embankment dams, levees, tailings dams held on 7th-9th September, 2016, at Colorado State University in Fort Collins, Colorado, USA. The increasing demand for dam and levee safety and flood protection has motivated new research and advancements and a greater need for cost-effective measures in overtopping protection as a solution for overtopping concerns at levees and dams. This seminar will bring together leading experts from practice, research, development, and implementation for two days of knowledge exchange followed by a technical tour of the Colorado State University Hydraulic Laboratory with overtopping flume and wave simulator. This seminar will focus on: Critical issues related to levees and dams; New developments and advanced tools; Overtopping protection systems; System design and performance; Applications and innovative solutions; Case histories of overtopping events; Physical modeling techniques and recent studies; and Numerical modeling methods.
Keywords: riprap design; interstitial flow; critical shear stress